Adventitious root formation in the cloned microcuttings of Prunus avium - Branka Pevalek-Kozlina; Sibila Jelaska (Acta Biologica Slovenica, 1989)
The rhizogenesis of the wild cherry shoots cloned in vitro has been investigated. The best re sults (70-90 % rooting) in the in vitro conditions were achieved by placing the shoots on an agar solidi fied mod. WPM medium supplemented with 2% sucrose and 4.9 µM IBA under a regime of 16/8 hr light/dark photoperiod at 24° ± 2°C, and illuminated by white fluorescent lamps.